2014
DOI: 10.1093/mnras/stu1236
|View full text |Cite
|
Sign up to set email alerts
|

Radio-mode feedback in local AGNs: dependence on the central black hole parameters

Abstract: Radio mode feedback, in which most of the energy of an active galactic nucleus (AGN) is released in a kinetic form via radio-emitting jets, is thought to play an important role in the maintenance of massive galaxies in the present-day Universe. We study the link between radio emission and the properties of the central black hole in a large sample of local radio galaxies drawn from the Sloan Digital Sky Survey (SDSS), based on the catalogue of Best & Heckman (2012). Our sample is mainly dominated by massive bla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
2
20
1
Order By: Relevance
“…In the radio luminosity comparison, we found a marginally higher, on average, radio luminosity for low-f AGN . These results seem inconsistent with the general picture of AGN luminosity increasing with increasing radio luminosity (Sikora & Begelman 2013;Ishibashi et al 2014), since the bulk of the energy is released from AGN in a kinetic form via radio jets (Churazov et al 2005). However, these studies are mainly focused on the powerful RAGN L 1.4GHz > 10 25 , much higher than the radio luminosity of our sample.…”
Section: Agn Powercontrasting
confidence: 86%
“…In the radio luminosity comparison, we found a marginally higher, on average, radio luminosity for low-f AGN . These results seem inconsistent with the general picture of AGN luminosity increasing with increasing radio luminosity (Sikora & Begelman 2013;Ishibashi et al 2014), since the bulk of the energy is released from AGN in a kinetic form via radio jets (Churazov et al 2005). However, these studies are mainly focused on the powerful RAGN L 1.4GHz > 10 25 , much higher than the radio luminosity of our sample.…”
Section: Agn Powercontrasting
confidence: 86%
“…This is consistent with the theory of hot accretion flows which predict the ubiquity of outflows in hot accretion mode systems (Narayan & Yi 1995;Yuan & Narayan 2014). The fraction of galaxies that host radio AGN is a strong function of galaxy stellar mass (Best et al 2005;Brown et al 2011;Janssen et al 2012;Rees et al 2016), black hole mass (Ishibashi et al 2014, Barišić et al 2017) and optical luminosity (Jiang et al 2007). It is also reported that the brightest galaxies within groups or clusters are more likely to host radio AGN than other galaxies with the same stellar mass (Von der Linden et al 2007;Best et al 2007).…”
Section: Introductionsupporting
confidence: 84%
“…In general, Seyfert galaxies and RQ AGN show a larger excess of line emission (at a given radio-core luminosity) than those of RL objects, i.e. L radio /L [O iii] < 10 −2 (Capetti & Balmaverde 2007;Ishibashi et al 2014). Since the LeMMINGs sample contains a more heterogeneous mixture of early-and late-type galaxies than the sample used by , and RL AGN are known to be associated with the most massive BHs 5 (Chiaberge & Marconi 2011), we select the RL galaxies (black circles, Fig.…”
Section: Radio Loudnessmentioning
confidence: 99%